NATURE OF INDUSTRY, KETIDAKEFEKTIFAN PENGAWASAN, DAN KECURANGAN LAPORAN KEUANGAN: MODERASI TEKNOLOGI INFORMASI - Ayu Fitaloka Waqidatun (2021)
This research aims to analyze the effect of nature of industry, ineffective monitoring on fraudulent financial statements moderated by information technology in 65 manufacturing companies listed on the Indonesia Stock Exchange in the period 2018-2020. This type of this research is quantitative research that uses secondary data based on annual report. Technique analyzing panel data in this research used regression model selection test, classical assumption test, and multiple linear regression which is processed using the STATA version 16 data processing application. Based on the test results and analysis, it can be concluded that (1) nature of industry has a negative and significant effect on fraudulentfinancial statement, (2) ineffective monitoring has no effect on fraudulent financial statement, (3) information technology can moderate the nature of industry relationship to financial statement fraud, and (4) information technology cannot moderate the relationship between ineffective monitoring and financial statement fraud.